Analisis Sosial Dan Hukum Terhadap Kasus Pernikahan Dini Dalam Perspektif UU Nomor 16 Tahun 2019 - Pancoko, Adi (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2024)
Abstract Early marriage in Indonesia remains a significant social issue despite the enactment of Law No. 16 of 2019, which sets the minimum marriage age. This study aims to analyze the social and legal factors influencing early marriage and evaluate the effectiveness of the law in addressing this issue, particularly concerning child marriage dispensation. A qualitative approach with a case study design was used, collecting data through in-depth interviews, legal document analysis, and social media observations. The findings reveal that social, cultural, and religious factors that continue to support early marriage, along with the influence of social media on adolescent perceptions, pose major challenges to reducing early marriage rates. Although Law No. 16 of 2019 stipulates a minimum marriage age, its implementation faces obstacles, especially with frequent dispensations requested in court. This study highlights the need for enhanced legal education, comprehensive sexual education, and family supervision to support existing policies and reduce early marriage rates in Indonesia.